Green supply chain management: an advanced corporate environmental governance practice in an automotive case firm / Noor Sufiawati Khairani - Khairani, Noor Sufiawati (Institute of Graduate Studies, UiTM, 2015)
Green supply chain management [GSCM], recognised as an advanced corporate environmental governance [CEG] practice in this study, has gained widespread recognition as a corporate strategy to address firms’ environmental obligations. However, studies which examine this phenomenon in an accounting context are limited. The thesis addresses this gap in the literature by examining four fundamental GSCM issues: the procedure and practices involved in the GSCM deployment; the key CEG components for the deployment of GSCM; the development of environmental performance measurement system [e-PMS]; and, the role of accountants in the deployment of GSCM. The research issues are examined through a single case study, PROTON Tanjung Malim Sdn Bhd [PTMSB], a car manufacturing and assembly firm operating in Malaysia. . Drawing from the literature, a proposed interpretive GSCM framework is used to analyse and discuss the first research issue. As proposed in the Interpretive GSCM framework, the case findings affirm that the procedure-led Plan-Do-Check-Act [PDCA] ISO 14001 Environmental Management System [EMS] framework facilitates the deployment of GSCM at the case firm. The framework postulates ten GSCM practices associated with the procedure-led PDCA-ISO 14001 EMS framework. However, only six GSCM practices, viz green purchasing, green inbound logistics, green manufacturing, green building, green waste management, and inverse flow practice were found at PTMSB. The thesis next explores the fundamental CEG elements required for the deployment of GSCM. Towards this aim, a proposed interpretive e-5Ps CEG framework is used to analyse and discuss the findings…